Spatial and Non-linear Dynamics of Environmental Tax, Technology, and Economic Growth on Carbon Dioxide Emissions in OECD Countries - MALAK, Assaf; TAHER, Hanady (Journal of Environmental Management and Tourism, 2024)
The current study sought to investigate spatial and non-linear dynamics of environmental tax, technology, and economic growth on carbon dioxide emissions in OECD Countries. Guided by STIRPAT as the theoretical framework and using OECD data between 2000 and 2021, the study also used the SAR model to investigate spatial dependence. The STIRPAT model is widely applied in environmental impact assessment to help scholars understand the forces that drive environmental issues. The analysis revealed that only economic growth significantly predicts CO2 emissions among OECD countries. Both ABAT and E.T. did not significantly affect CO2 emissions in the OECD countries. The SAR model revealed the presence of spatial dependence. This means other countries with higher emissions are also likely to have neighbours with higher emissions, and vice versa. This means there are spillover effects, where technology advancements and environmental policies in one country or region could influence emissions in other countries, especially neighbouring countries.